Historical aspects and perspectives of electrosurgery (literature review) - Muzichenko, Petro; Cherniak, Viktor; Lankin, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The historical milestones of electrosurgery are reviewed. Traced many years through the creation and introduction of technologies of surgical treatment of patients with the use of electricity from the time of its invention and the first devices to receive it with modern devices for use in electrosurgery. The authors noted a significant contribution of outstanding engineers working in research and improve the use of electricity in the different sections of engineering and medicine. One of the outstanding geniuses end of IX <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">–<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> beginning of XX century was Nikola Tesla, who in 1891 published observations about the thermal effect during passage through the human body high frequency alternating currents obtained by generator constructed it. Tesla first demonstrated that high-frequency currents have irritating action, despite the great tension, and well tolerated by the human body, while the current of similar strength, but lower frequency is detrimental to him. This discovery was a significant impetus for the development of electrosurgery. Based on the developments of Nikola Tesla designed devices that are used in medicine today. The end of the twentieth century was marked undefined another discovery, which helped create a new trend in surgery — using electric medicine, sponsored by the genius of the twentieth century XI NAS of Ukraine Paton B. E. In the article the positive factors electrosurgery, given its shortcomings, which are caused by lack of understanding of the impact of electricity on the human body in general and cellular structures in the area of electricity. To address these problems should be involved in research specialists from different fields, including engineers, electrical engineers, biologists, biophysicists and doctors of various specialties.